Facebook's transformation from a social network into a media platform and its implications for the new media landscape - Mounia Dahdouh (Social Empowerment Journal, 2021)
This research work  aims to shed light on the new media trends of social networks, particularly Facebook, in order to show the manifestations of the transformation, which led to repercussions that put the network under pressure as well as changed the profile of the global media landscape.The results show that Face-book became a news platform and this fact enabled it to achieve its profitability endeavors as well as the latest wholesale changes in standards governing the changing media practice.This shift has also created several crises that have affected the international media, including the Algerian ones as well as the same network level, which withdrew from the field in contexts it had created to use as an influencing tool, but instead it was affected by it as well.